YOUNG TRANSLATOR’S WORKSHOP: translations of Spanish philosophical lyrics by Serhiy Savoshchenko - Pokora, Anastasia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
YOUNG TRANSLATOR’S WORKSHOP: translations of Spanish philosophical lyrics by Serhiy Savoshchenko